30‐Day Emergency Department Revisit Rates among Older Adults with Documented Dementia. Issue 11 (12th August 2019) - Kent, Tyler; Lesser, Adriane; Israni, Juhi; Hwang, Ula; Carpenter, Christopher; Ko, Kelly J.
Abstract : OBJECTIVES: Published literature on national emergency department (ED) revisit rates among older adults with dementia is sparse, despite anecdotal evidence of higher ED utilization. Thus we evaluated the odds ratio (OR) of 30‐day ED revisits among older adults with dementia using a nationally representative sample. DESIGN: We assessed the frequency of claims associated with a 30‐day ED revisit among Medicare beneficiaries with and without a dementia diagnosis before or at index ED visit. We used a logistic regression model controlling for dementia, age, sex, race, region, Medicaid status, transfer to a skilled nursing facility after ED, primary care physician use 12 months before index, and comorbidity. SETTING: A nationally representative sample of claims data for Medicare beneficiaries aged 65 and older who maintained continuous fee‐for‐service enrollment during 2015 and 2016. Only outpatient claims associated with an ED visit between January 2016 and November 2016 were included as a qualifying index encounter. PARTICIPANTS: We identified 240 249 patients without dementia and 54 622 patients for whom a dementia code was recorded in the year before the index encounter in 2016. RESULTS: Our results indicate a significant difference in unadjusted 30‐day ED revisit rates among those with an ED dementia diagnoses (22.0%) compared with those without (13.9%). Our adjusted results indicated that dementia is a significant predictor of 30‐day ED revisits ( P  < .0001). Those with a dementia diagnosis at or before the index ED visit were more likely to have experienced an ED revisit within 30 days (OR = 1.27; 95% confidence interval = 1.24‐1.31). CONCLUSION: Dementia diagnoses were a significant predictor of 30‐day ED revisits. Further research should assess potential reasons why dementia is associated with markedly higher revisit rates, as well as opportunities to manage and transition dementia patients from the ED back to the community more effectively. J Am Geriatr Soc 67:2254–2259, 2019